Adsorption of Methylene Blue in Acoustic and Magnetic Fields by Porous Carbon Derived from Sewage Sludge - Wenzhong Shen; Qingjie Guo; Xiangping Yang; Yihong Liu; Yanru Song; Jian Cheng (Adsorption Science & Technology)
After KOH activation, the pyrolysis residues of sewage sludge could be converted to a porous carbon with a pore size situated mainly in the 0.6–1.5 nm range. The adsorption rate and capacity of the porous carbon towards Methylene Blue could be improved by the use of acoustic and magnetic fields. The best adsorption behaviour was displayed when the acoustic field frequency was 50 Hz and the magnetic field strength was 485 mT.